1998
DOI: 10.1253/jcj.62.7
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Serum Cholesterol and the Risk of Acute Myocardial Infarction in a Screened Cohort in Okinawa, Japan

Abstract: Coronary heart disease (CHD) is rare in Japanese subjects and serum cholesterol levels are low. However, no data have been published relating the effect of serum cholesterol levels to the incidence of acute myocardial infarction (AMI) in Japan. Data from a large community-based mass screening registry are available for the geographically isolated island of Okinawa, Japan (1980 census, 1.11 million). A total of 38,053 participants (17,859 men and 20,194 women) whose serum cholesterol levels were determined in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 33 publications
2
23
1
Order By: Relevance
“…However, the relationship between risk factors and CAD among young middle-aged Japanese men was not examined. In agreement with a number of previous studies, the present study demonstrated that the increase in TC was proportionally associated with a higher incidence of CAD (17,18 (17,18) as well as in a study in Japan, which included the elderly subjects (19). Therefore, the present study has confirmed that TC is a significant risk factor for CAD also in young middle-aged Japanese men.…”
Section: F I D E N C E I N T E R V a L S F O R F A S T I N G P L A S supporting
confidence: 93%
“…However, the relationship between risk factors and CAD among young middle-aged Japanese men was not examined. In agreement with a number of previous studies, the present study demonstrated that the increase in TC was proportionally associated with a higher incidence of CAD (17,18 (17,18) as well as in a study in Japan, which included the elderly subjects (19). Therefore, the present study has confirmed that TC is a significant risk factor for CAD also in young middle-aged Japanese men.…”
Section: F I D E N C E I N T E R V a L S F O R F A S T I N G P L A S supporting
confidence: 93%
“…After the exclusion of death due to liver disease during the entire follow-up period, increased HR in the lowest TC group disappeared and the HR for total mortality within the first 5 years of follow up in the highest TC group further increased (HR 1.48; 95%CI 1.12-1.96), mainly as a consequence of CHD. These results were similar in gender-specific analysis, and were in good agreement with the Okinawa cohort study where mortality from CVD is the lowest and life expectancy is the highest in Japan 26) . On the other hand, hypercholesterolemia was not a risk factor for stroke, which is in good agreement with the Hisayama Study, an established cohort study 27) , and the mortality from cerebral hemorrhage was even the highest in the lowest TC group in men (HR 3.77; 95% CI, 1.35-10.5).…”
Section: Hypercholesterolemia and Chdsupporting
confidence: 88%
“…, MHW Primary Hyperlipidemia 26) , Okinawa cohort 27) and Ehime epidemiological 10) studies and epidemiological studies conducted in 76 workplaces in Japan (the 3M Study) 4) , have confirmed that the relative risk of CAD increases continuously in association with increases in the levels of LDL-C and TC.…”
Section: Hyper-ldl Cholesterolemiamentioning
confidence: 93%